The Effect of Motivational Abdominal Breathing Device on Breathing Patterns and Shortness of Breath in Patients with Chronic Obstructive Pulmonary Disease - Haji Mohammad Norozi; Mehdi Golmohammadi Kavaki; Fatemeh Hajiabadi; Hamidreza Behnam Vashani (Mashhad University of Medical Sciences, 2017)
Background and purpose: Despite the high prevalence of chronic obstructive pulmonary disease, There haven,t been definite curative treatment for the disease and focus of treatment has directed towards pulmonary rehabilitation as an effective non-drug treatments. this study were performed to determine the effect of motivational abdominal breathing device on breathing pattern and dyspnea of chronic obstructive pulmonary disease Materials and methods: This study is a clinical trial done in 2015 on 70 patients with chronic obstructive pulmonary disease admitted to Samen alaeme hospital, CHENARAN city. Patients were assigned to two groups of 35 persons, Intervention and control. groups did exercises at home twice a day for two weeks. The dyspnea, respiratory rate and depth of breathing, before, seventh day and after the intervention was measured by spirometry and dyspnea NRS scale. Data analysis was performed by SPSS version 11.5 using t-test, Mann-Whitney and repeated measures analysis. Results: The results showed that difference in respiratory rate before and after intervention (P=0/78) did not change significantly between two groups. But difference before and after the intervention, depth of breathing and before and after intervention of dyspnea were significantly changed in both groups (P